Introduction to the Application of Kaizen Principles in the World of Work, For the Students of SMK.N 43 Jakarta - Lis Lesmini; Vica Nurhayani; Tri Mulyani Setyowati; Dian Anom Baskoro; Krisman Damanik (Greenation Publisher & Yayasan Global Resarch National, 2024)
The purpose of this activity is to provide an introduction to the application of Kaizen principles in the world of work for the students of SMK.N 43 Jakarta. This activity is part of an effort to introduce the concept of continuous improvement to students because the Kaizen principle has great relevance in the context of the ever-changing modern world of work as well as in the daily lives of students. The activity was carried out directly at SMK.N 43, on Wednesday 7 February 2024 through the provision of basic Kaizen knowledge, case examples, video screenings, games and interactive discussions. The activity was attended by 40 people, consisting of 35 students, 4 ITL Trisakti Team Lecturers, and 1 student. From the results of the interview, it is known that the partner's problem is the desire to increase students' knowledge of the principles that apply in the world of work. Based on the results of the analysis of the pre-test and post-test, each of which consists of 10 indicators, it is found that there is an increase in participant understanding between 22% to 101%, with an average increase in understanding of 63.1% for each indicator.